Analysis of Promotional Strategies in Effort to Increase Sales of Astra Motor Purworejo - Rahmadani, Hana Novia; Anas Hidayat (Publikasi Inspirasi Indonesia, 2024)
This Astra Motor Purworejo retail store sells several products from the superior motorbike segment. One of Astra Motor's advantages is that consumers can choose vehicle products based on brand, color, and type according to their tastes and needs. Promotional activities carried out by distributing brochures are less effective because the majority of people now only see the brochure and throw it away or tear it up. Astra Motor Purworejo has used social media, but not as optimally as expected. The aim of this internship is to learn promotional strategies to increase sales targets for Astra Motor Purworejo. Internships also provide students with the opportunity to adapt to the work environment and work discipline. This study found that advertising, sales promotion, personal selling, public relations, and direct marketing were quite effective. However, promotional activities create a good relationship between the company and consumers, and the marketing of Astra Motor Purworejo motorbike products must make advertising better by utilizing the various types of media available, which will further increase sales.